Potencial alelopático e levantamento do banco natural de sementes sob a copa de Copaifera langsdorffii Desf - da Silva, Regildo Márcio Gonçalves [UNESP]; dos Santos, Valter Henrique Marinho [UNESP]; Borges, Fabiano Marcelino; de Melo, Fabiano de Fátima Queiroz; Silva, Luciana Pereira [UNESP] (My University, 2012)
The aim of this study was to evaluate the allelopathic effect of soil samples collected under the canopies of three specimens of Copaifera langsdorffii the germination of Lactuca sativa and survey the natural seed bank according to seasonality. To test the allelopathic effect was carried experiments of pre and post-emergence with seeds of L. sativa and to quantify the stock of seeds, soil samples were collected from three specimens at three distances from the stem (1, 2 and 3 m) and at three depths (0-5, 5-10 and 10-15cm) in the region of savanna in the dry and wet seasons. The samples tested in bioassay of pre-emergence no significant influence on germinability, mean germination time and mean germination speed, but showed a difference in the synchronism of germination, these data were independent of sampling station. In test for post-emergence was observed statistical difference in the parameters evaluate (length of primary roots and hypocotyls) in both seasons. To quantify the natural seed bank were macroscopic analysis of each soil sample with the help of stereoscopic microscope. The analysis of the natural seed bank showed a larger number of seeds in the 0-5cm and in distance of 2m for both seasons. The results suggest the presence of allelochemical substances in soil samples collected under the canopy of Copaifera langsdorffii.
Allelopathic potential and survey of natural seed bank under the canopy of Copaifera langsdorffii Desf
Keywords: Copaiba; Lettuce; Post-emergence; Pre-emergence; Seed bank